Perlawanan Harian Perempuan untuk Percepatan Kebijakan Tanah Objek Reforma Agraria (TORA) dan Perhutanan Sosial (PS) - Kasmiati Kasmiati; Ganies Oktaviana (Yayasan Jurnal Perempuan, 2022)
This paper analyzes the women’s everyday forms of resistance, in formal and informal spaces, to the acceleration of the Land Objects of Agrarian Reform (‘Tanah Objek Reforma Agraria’—TORA) and Social Forestry (SF) policies in Sigi Regency in Central Sulawesi. The women’s resistance is a broader manifestation of To-Kaili philosophy regarding the role of women as the center and base in maintaining harmony between God, humans, and nature, including in the management of agrarian resources (‘sumber-sumber agraria’—SSA). Women who are fighting for gender-based agrarian justice still encounter some obstacles, including limited awareness of genderbased agrarian justice and the challenge of the resistance not yet being dominant.